Cattle Fattening Program by PT Pertamina Hulu Energi North Sumatera Offshore: Factors Underlying the CSI Score in Muara Satu District, Aceh Province - Putranto, Nurseno Dwi; Ayuni, Rara; Vernanda, Rani Noor; Ulfah, Nurhayatul (Global Writing Academica Researching and Publishing, 2024)
The Community Satisfaction Index (CSI) is a crucial element in any community empowerment program. The community empowerment program conducted by the Corporate Social Responsibility (CSR) of PT Pertamina Hulu Energi North Sumatera Offshore (PHE NSO) has been successfully implemented with a very high or very satisfactory CSI score of approximately 84.29%. However, these results remain statistical, and exploring the underlying non-statistical factors is highly relevant or important. This study aims to identify the factors underlying the CSI score in the cattle fattening program by CSR PT PHE NSO in Muara Satu District, Aceh Province. To achieve this goal, a qualitative descriptive approach with document analysis was employed. The study results reveal 27 main factors underlying the CSI score of the Cattle Fattening Program by CSR PT PHE NSO. These 27 factors were narrowed down into 4 main aspects, including: 1) active involvement of all parties such as the company, community, and program facilitators (CSR); 2) careful planning based on factual data, including needs analysis, participatory program design, and continuous evaluation; 3) transparent and accountable program implementation, including prudent financial management and continuous monitoring and evaluation; and 4) local program development, such as meeting community needs and empowering the community to have or develop independent capacity.